Transformation of the Indonesian Language Game (GABIN) Digital Assessment for Evaluating Class V Elementary Students' Paragraph Comprehension - Kristanti, Anisa; Rahmawati, Fitri Puji (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This research aims to develop a Digital Assessment of Indonesian Language Games (GABIN) to evaluate paragraph comprehension among fifth-grade students. Methodology: A qualitative Research and Development (R&D) approach was employed using the ADDIE model, focusing on the Analysis, Design, and Development stages. The research subjects were fifth-grade students at Muhammadiyah Special Program Kottabarat Elementary School. Data collection techniques included observation, interviews, and documentation. Results: The research resulted in a gamification-based learning evaluation tool (GABIN) designed to assess paragraph comprehension. The tool was validated as "very feasible" by both media experts and educational assessment experts, each awarding a score of 87.5%. These findings support the conclusion that the GABIN assessment tool is highly suitable for evaluating paragraph comprehension skills in grade V students. Applications/Originality/Value: This study demonstrates the integration of gamification into educational assessment and contributes a novel digital tool for Indonesian language instruction. GABIN offers a user-friendly, engaging alternative for measuring students’ reading comprehension in the classroom context, especially in upper elementary levels.